2004
DOI: 10.1302/0301-620x.86b5.14469
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of open and percutaneous techniques in the surgical treatment of tennis elbow

Abstract: We conducted a prospective, randomised, controlled trial of 45 patients (47 elbows), with tennis elbow, who underwent either a formal open release or a percutaneous tenotomy. All patients had pre- and post-operative assessment using the Disability of Arm, Shoulder and Hand (DASH) scoring system. Both groups were followed up for a minimum of 12 months. Statistical analyses using the Mann-Whitney U test and repeated measured ANOVA showed significant improvements for patient satisfaction (p = 0.012), time to retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
118
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 9 publications
2
118
1
3
Order By: Relevance
“…Percutaneous extensor tenotomy for chronic tennis elbow preformed as an office procedure under local or general anaesthesis is a simple procedure resulting in good result, quick recovery and minimal complications [13][14][15]. Dunkow et al reported better results and quicker recovery with precutaneous release in a radomised comparative trial…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous extensor tenotomy for chronic tennis elbow preformed as an office procedure under local or general anaesthesis is a simple procedure resulting in good result, quick recovery and minimal complications [13][14][15]. Dunkow et al reported better results and quicker recovery with precutaneous release in a radomised comparative trial…”
Section: Discussionmentioning
confidence: 99%
“…between percutaneous and open releases [14]. Difficulty in visualisation and isolating ECRB tendon from common extensor origin is a drawback with percutaneous tenotomy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Bir yıllık izlemde, cerrahi uygulanan farklılıklar içermektedir. [72,73] Şok dalga tedavisi ile lateral epikondilit tedavisinde de %90,9'a varan başarılı sonuçlar bildirilmiştir. İnvaziv bir girişim olmaması ve bildirilen düşük komplikasyon oranları kullanım sıklı-ğını arttırmıştır.…”
Section: Lateral Epi̇kondi̇li̇t Tedavi̇si̇nde şOk Dalga Uygulamalariunclassified
“…However, with the advent of percutaneous techniques, shorter procedural times and improved aesthetic outcomes became possible. Furthermore, there is evidence to suggest that percutaneous tenotomy is as safe and effective as the open procedure.It is notable that the extent of the tendinous portion divided in the muscle of interest appears directly correlated with increased postoperative mobility [54,55] . In animal studies, ultrasoundguided percutaneous tenotomy has been shown to increase complete tendon transection and decrease damage to surrounding structures compared to palpation-guided tenotomy (63).…”
Section: Percutaneous Tenotomymentioning
confidence: 99%
“…A brief listing of clinical indications and contraindications for percutaneous tenotomy are listed in Table 5. A comprehensive discussion of this topic is beyond the scope of this review [53][54][55][56][57][58][59][60][61][62][63] . Percutaneous tenotomy is ideally performed at the bedside or in an outpatient setting.…”
Section: Percutaneous Tenotomymentioning
confidence: 99%